Effect of isokinetic dynamometer velocity on muscle strength deficit in elite athletes after ACL reconstruction - Kadija, M.; Knezevic, O.; Milovanovic, D.; Bumbasirevic, M.; Mirkov, D. M. (Medicina dello Sport, 2011)
Aim. Although many studies on anterior cruciate ligament (ACL) postoperative deficits have reported the strength test measurements obtained at one or two angular velocities, there is no clear evidence which testing velocities result in the most sensitive outcome for particular variables, as well as how these variables are affected by the applied angular velocity. The aim of this study was to assess the effect of velocity on the disbalances of the muscle strength as assessed by the hamstrings to quadriceps peak torque ratio (H:Q ratio) and their relative strength deficit (RSD).